2019
DOI: 10.1111/pace.13691
|View full text |Cite
|
Sign up to set email alerts
|

Impact of recanalization of chronic total occlusion on left ventricular electrical remodeling

Abstract: BackgroundSuccessful percutaneous coronary intervention (PCI) for chronic total occlusion (CTO) is associated with reduction of cardiac mortality, as well as reducing fatal ventricular arrhythmias. The aim of this study was to evaluate the effect of recanalization of CTO on endocardial left ventricular voltages by paired electrophysiological studies.MethodsSixteen consecutive patients who underwent PCI for de novo CTO lesions were included. High‐density mapping was performed during sinus rhythm before and 8 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 38 publications
1
7
0
1
Order By: Relevance
“…Thus, it is legitimate to expect that the chronic ischemia associated with IRACTO might have an effect on scar remodeling and that, in turn, the recovery of normal coronary flow may impact this remodeling and the electrical properties of the scar. Emerging evidence would support this hypothesis: two independent research groups have performed electro‐anatomical mapping before and after percutaneous revascularization of an IRACTO in small series of patients and they have both observed a reduction in scar area after IRACTO revascularization 17,18 . Interestingly, a significant change in the electrical properties of the scar was already observed immediately after IRACTO revascularization and it further increased after 6 months 17 .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Thus, it is legitimate to expect that the chronic ischemia associated with IRACTO might have an effect on scar remodeling and that, in turn, the recovery of normal coronary flow may impact this remodeling and the electrical properties of the scar. Emerging evidence would support this hypothesis: two independent research groups have performed electro‐anatomical mapping before and after percutaneous revascularization of an IRACTO in small series of patients and they have both observed a reduction in scar area after IRACTO revascularization 17,18 . Interestingly, a significant change in the electrical properties of the scar was already observed immediately after IRACTO revascularization and it further increased after 6 months 17 .…”
Section: Discussionmentioning
confidence: 97%
“…Given the observational nature of the study and the lack of wide band protocols to avoid ICD artifacts at cardiac magnetic resonance, non‐invasive evaluation of the scar before and after IRACTO revascularization was not performed, so the present study do not provide direct information about the possible process of scar remodeling after IRACTO revascularization. However, other reports suggest the existence of such remodeling 17,18 …”
Section: Limitationsmentioning
confidence: 90%
See 1 more Smart Citation
“…After CTO revascularization there is immediate decrease in scar border zone area. Furthermore, there is improvement of markers of heterogeneity of repolarization as reflected by QT dispersion [41,42]. It is known that heterogenous ventricular repolarization is associated with an increased risk for ischemia-related VA after myocardial infarction [43].…”
Section: Proarrhythmogenic Substrate In Cto Territorymentioning
confidence: 99%
“…Interestingly, recent 3D electro-anatomically mapping studies demonstrated reduction of the area of the scar border zone after successful CTO PCI [42,62]. Yamashita et al performed high-density endocardial mapping during sinus rhythm before and 8 months after CTO PCI in 16 patients [42]. Thirteen patients had a successful CTO PCI and no restenosis; 3 patients had a failed CTO PCI or in-stent occlusion during follow-up.…”
Section: Cto Revascularization Lowers Arrhythmic Riskmentioning
confidence: 99%